Neurobehavioral Activity Study of Methanolic Whole Plants Extract of Cyperus rotundus Linn. (Journal of Pharmaceutical Negative Results, 2019)
Background: Cyperusrotundus commonly known as “nutgrass” is extensively used in traditional Chinese and Indian Ayurvedic medicine. It istraditionally used to treat fevers, digestive disorders, wound, and bruises. Materials and Methods: This study evaluated the sedative-hypnoticand antidepressant effect of the methanolic extract of C. rotundus(MECR). To perform this study, the whole plants of C.rotundus were taken forextraction with methanolfollowing soaking process and tested for acute toxicity on mice first.The sedative and hypnotic activity were then studiedperforming hole board and open field testsin albino mice model at the doses of 100 and 200 mg/kg body weight of MECR. Diazepam at the doseof 1 mg/kg was utilized as a standard drug in both experiments. Similarly, antidepressant activity test was also performed using forced swimmingtest and tail suspension test. Nortriptyline was used as a standard to assess antidepressant activity. Results: We found that MECR produced aninsignificant dose‑dependent effects against locomotors activity of mice both in hole cross and open field tests. Besides, it was also noticedafter analyzing forced swimming and tail suspension test that it has no significant antidepressant activity. Conclusion: Taken together, ourstudy suggests that MECR do not possess notable sedative-hypnotic and antidepressant or neurobehavioral properties.